The influence of bracket type on the external apical root resorption in class I extraction patients - a retrospective study - Fang Qin; Yu Zhou (BMC, 2019)
Abstract Background The relationship between orthodontic treatment-related factors and EARR has never been fully answered. The aim of this study was to investigate whether conventional and passive self-ligating brackets affect the amount and severity of external apical root resorption (EARR) in withdrawal patients. Methods Ninety-eight patients were selected from department of orthodontic, hospital of stamotology, Wenzhou medical university. Patients received treatment with either a conventional edgewise appliance (n = 49, Mini, 3 M Unitek, USA) or a passive self-ligating bracket system (n = 49, Damon, Ormco, USA). EARR of the maxillary incisors was evaluated on panoramic radiographs at the before and end of orthodontic treatment, respectively. Intergroup comparisons of root resorption were performed with Mann-Whitney tests. The univariate and multivariate regression model was used to assess the appliance type, age, sex and duration of treatment on EARR. Results There was no significant difference in the amount of EARR between the two groups was found. Age and gender were not association with EARR, however, EARR was positively correlated with treatment duration. Conclusions The type of bracket did not influence the occurrence and severity of the external apical root resorption in class I extraction patients.